2012
DOI: 10.1093/ckj/sfs031
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic osteomalacia illustrating the effect of fibroblast growth factor 23 on phosphate homeostasis

Abstract: In oncogenic osteomalacia (OOM), fibroblast growth factor 23 (FGF23) induces renal phosphate wasting and inhibits the appropriate increase of calcitriol. A patient suffering from OOM is described. Serum calcium, phosphate, biointact parathyroid hormone and intact FGF23 as well as the calcitriol and 24,25-vitamin D levels were measured before and after tumour removal. The clinical approach to a patient with hypophosphataemia is discussed and the changes in mineral metabolism after removal of a FGF23-producing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…FGF23 was first reported as a gene responsible for autosomal‐dominant hypophosphataemic rickets, and recently became widely accepted to encode a secreted protein that is particularly abundant in tumour‐associated osteomalacia cases . In the past, tumour‐associated osteomalacia was thought to be induced by several kinds of tumour, but a recent investigation revealed that almost all tumour‐induced osteomalacia cases were associated with a histologically definitive tumour entity, phosphaturic mesenchymal tumour, mixed connective tissue variant .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGF23 was first reported as a gene responsible for autosomal‐dominant hypophosphataemic rickets, and recently became widely accepted to encode a secreted protein that is particularly abundant in tumour‐associated osteomalacia cases . In the past, tumour‐associated osteomalacia was thought to be induced by several kinds of tumour, but a recent investigation revealed that almost all tumour‐induced osteomalacia cases were associated with a histologically definitive tumour entity, phosphaturic mesenchymal tumour, mixed connective tissue variant .…”
Section: Discussionmentioning
confidence: 99%
“…FGF23 was first reported as a gene responsible for autosomal-dominant hypophosphataemic rickets, 12 and recently became widely accepted to encode a secreted protein that is particularly abundant in tumour-associated osteomalacia cases. 6,13 In the past, tumour-associated osteomalacia was thought to be induced by several kinds of tumour, 14 but a recent investigation revealed that almost all tumour-induced osteomalacia cases were associated with a histologically definitive tumour entity, phosphaturic mesenchymal tumour, mixed connective tissue variant. 10 As to the metastatic potential of this condition, some metastatic cases were reported, 10,[15][16][17][18][19][20] but no comparative study was performed between metastatic and non-metastatic PMT-MCT cases with plural cases in the former group.…”
Section: Discussionmentioning
confidence: 99%
“…TIO has been described in association with adenocarcinomas of the ovary, lung, prostate, colon and head/neck ( Fatani et al, 2013 , Westerberg et al, 2012 , Gandhi et al, 2012 , Jiang et al, 2012 , Gardner et al, 2013 , Hautmann et al, 2014 , Lin et al, 2014 , Taylor et al, 1984 , Lee et al, 2014 , Ryan and Reiss, 1984 , Tarasova et al, 2013 , Kominek et al, 2011 , Luo et al, 2013 , Mathis et al, 2013 ). There has been one case report of a patient with thyroid cancer presenting with TIO and bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Successful surgical resection of the FGF-23 secreting tumor is curative, thus accurate localization of the tumor is of the utmost importance ( Jonsson et al, 2003 ). The majority of the TIO cases previously reported in the literature have been caused by small mesenchymal tumors derived from bone ( Fatani et al, 2013 , Westerberg et al, 2012 , Gandhi et al, 2012 ), soft tissue ( Jiang et al, 2012 ), skin ( Gardner et al, 2013 ) and cartilage ( Hautmann et al, 2014 ). TIO has also been reported in association with malignant adenocarcinomas of the ovary ( Lin et al, 2014 ), lung ( Taylor et al, 1984 ), prostate ( Lee et al, 2014 ), colon ( Ryan and Reiss, 1984 ) and head/neck ( Tarasova et al, 2013 , Kominek et al, 2011 , Luo et al, 2013 , Mathis et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%